Long term in vivo performance of starch-based scaffolds - Santos, T. C. (2008)
[Excerpt] Natural-based biomaterials are mainly constituted by proteins or polysaccharides which, under certain circumstances, may be recognized as natural host invaders. Starch-based scaffolds, produced by different methodologies, have been shown to hold adequate properties regarding mechanical performance and in vitro biocompatibility. This study aimed at evaluating the in vivo inflammatory response to starch-based scaffolds. [...]